1997
DOI: 10.1084/jem.185.2.293
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Induces Cytotoxic T Lymphocytes in the Cervix of Infected Women

Abstract: Although T lymphocytes are present in the genital mucosa, their function in sexually transmitted diseases is unproven. To determine if cervical T cells mediate HIV-specific cytolysis, mononuclear cells in cytobrush specimens from HIV-1-infected women were stimulated in vitro with antigen. Resultant cell lines lysed autologous targets expressing HIV-1 proteins in 12/19 (63%) subjects, and these responses were detected intermittently on repeated visits. All 8 subjects with blood CD4+ counts ⩾500 cells/μl had HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 37 publications
1
104
0
1
Order By: Relevance
“…Musey and colleagues have demonstrated that HIV-1-specific CTL (involving both CD4 ϩ and CD8 ϩ cells) could be generated from cervical specimens in HIV-1-infected women (20). In these HIV-1-infected women, comparisons of intraindividual cervical and blood CTL specificities also indicated that epitopes recognized by CTL in the cervix were commonly recognized in the blood, although relative frequencies of CTL in cervix and blood were not examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musey and colleagues have demonstrated that HIV-1-specific CTL (involving both CD4 ϩ and CD8 ϩ cells) could be generated from cervical specimens in HIV-1-infected women (20). In these HIV-1-infected women, comparisons of intraindividual cervical and blood CTL specificities also indicated that epitopes recognized by CTL in the cervix were commonly recognized in the blood, although relative frequencies of CTL in cervix and blood were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIV-1-specific CTL have been demonstrated in the genital tract of HIV-1-infected women (20), there are no previous data regarding mucosal CTL responses in the genital tract of exposed, uninfected populations. This may be partly due to the difficulties inherent in demonstrating low-frequency CTL using samples obtained from a site with a rich microbial flora and that contain relatively few T lymphocytes.…”
Section: T Is Now Recognized That There Is Variability In Susceptibmentioning
confidence: 98%
“…Only limited information is available on mucosal vaccine induction of CTL responses in mucosal tissues themselves, by using either peptidebased vaccines (19), live viruses (20,21,55), DNA vaccination (56), or targeted lymph node immunization (13,57). The development of vaccines capable of inducing CTL in mucosal sites, however, is becoming more critical with the emergence of recent evidence that natural genital infection with HIV-1 leads to the development of MHC class I-restricted cytotoxic T cells in the cervix (17) and that mucosal administration of live attenuated SIV, which protects against subsequent infection with virulent virus, elicits a CTL response in gut-associated lymph nodes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of candidate HIV vaccines that are designed to elicit mucosal immune responses have so far focused mainly on HIV-induced B cell (IgA) and Th cell responses (13)(14)(15) or CTLs in the spleen (16). While recent findings underscore the need for vaccines capable of inducing CTL in mucosal sites (17)(18)(19)(20)(21)(22), the knowledge necessary to create them remains scarce. Only a few vaccine approaches for HIV have been shown to induce a CTL response in the mucosa (19 -22).…”
mentioning
confidence: 99%
“…Although it would be difficult to obtain suitable T cell samples, HLA class I tetramers could greatly facilitate attempts to characterize the Ag specificity of intraepithelial and submucosal T lymphocytes that are present in the cervix of Ct-infected women. It is encouraging in this respect that cervical T cells obtained from HIV-1-infected women have been successfully used to establish a functional role for HLA-restricted T cells in cervical infections and that the HLA restriction elements and epitope specificities of peripheral and cervical CTLs were similar in given individuals (45).…”
Section: Discussionmentioning
confidence: 99%